1997
DOI: 10.1183/09031936.97.10081780
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and respiratory symptoms in 6-7 yr old Italian children: gender, latitude, urbanization and socioeconomic factors. SIDRIA (Italian Studies on Respiratory Disorders in Childhood and the Environment)

Abstract: Asthma and respiratory symptoms in 6-Wheeze in the last 12 months was reported for 9% of males and 6% of females, and severe wheezing attacks for 1.4 and 0.8%, respectively. Asthma during lifetime was reported for 11% of males and 6.4% of females. The prevalence of physician-diagnosed asthma increased with level of urbanization, but reported wheezing did not, suggesting a labelling bias. Socioeconomic status was not associated with the prevalence of most wheezing symptoms or of physician-diagnosed asthma, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…Nitrogen dioxide (NO 2 ) was measured at 70 schools in a cross sectional study on children conducted in 1995 (Italian Study on Respiratory Diseases and Environment), the Italian part of the International ISAAC study [22]. The objective of the measurement campaign was to estimate average NO 2 exposure at schools in Rome and the 70 schools were a random sample of all primary and junior high schools of the city (stratified by the 20 city districts).…”
Section: Methodsmentioning
confidence: 99%
“…Nitrogen dioxide (NO 2 ) was measured at 70 schools in a cross sectional study on children conducted in 1995 (Italian Study on Respiratory Diseases and Environment), the Italian part of the International ISAAC study [22]. The objective of the measurement campaign was to estimate average NO 2 exposure at schools in Rome and the 70 schools were a random sample of all primary and junior high schools of the city (stratified by the 20 city districts).…”
Section: Methodsmentioning
confidence: 99%
“…Anandan et al [8] have shown that there is no overall decline in the prevalence of suggestive symptoms of asthma, and in Italy, during the past 20 years, prevalence has raised by 38% [9]. In the framework of the International Study of Asthma and Allergies in Childhood (ISAAC) Project [10], the first SIDRIA (Italian Studies of Respiratory Diseases in Childhood and the Environment) survey in children and adolescents (6–7 and 13–14 years old) was carried out in 10 areas of northern and central Italy [11,12], reporting a lifetime prevalence of 9.1%. In 2002, a second multicentre study including some areas of southern Italy reported a slightly higher prevalence of 9.5% [13].…”
Section: Introductionmentioning
confidence: 99%
“…The SIDRIA project – Studi Italiani sui Disturbi Respiratori nell'Infanzia e l'Ambiente [14-16] – is a large multi-center, population-based study conducted in the framework of the International Study of Asthma and Allergies in Childhood (ISAAC) [17]. The findings from SIDRIA-1, conducted in 1994–1995, showed a positive association between indicators of air pollution from heavy vehicular traffic in the street of residence and a wide range of respiratory disorders in children living in highly urbanized areas [18].…”
Section: Introductionmentioning
confidence: 99%